Single-molecule LATE-PCR analysis of human mitochondrial genomic sequence variations. - Adam Osborne (Public Library of Science (PLoS), 2009)
It is thought that changes in mitochondrial DNA are associated with many degenerative diseases, including Alzheimer's and diabetes. Much of the evidence, however, depends on correlating disease states with changing levels of heteroplasmy within populations of mitochondrial genomes, rather than individual mitochondrial genomes. Thus these measurements are likely to either overestimate the extent of heteroplasmy due to technical artifacts, or underestimate the actual level of heteroplasmy because only the most abundant changes are observable. In contrast, Single Molecule (SM) LATE-PCR analysis achieves efficient amplification of single-stranded amplicons from single target molecules. The product molecules, in turn, can be accurately sequenced using a convenient Dilute-'N'-Go protocol, as shown here. Using these novel technologies we have rigorously analyzed levels of mitochondrial genome heteroplasmy found in single hair shafts of healthy adult individuals. Two of the single molecule sequences (7% of the samples) were found to contain mutations. Most of the mtDNA sequence changes, however, were due to the presence of laboratory contaminants. Amplification and sequencing errors did not result in mis-identification of mutations. We conclude that SM-LATE-PCR in combination with Dilute-'N'-Go Sequencing are convenient technologies for detecting infrequent mutations in mitochondrial genomes, provided great care is taken to control and document contamination. We plan to use these technologies in the future to look for age, drug, and disease related mitochondrial genome changes in model systems and clinical samples.